The Economic Issues of Compulsory Health Insurance: Further Comment - Netzer, D. (Quarterly Journal of Economics, 1952)
Journal Article The Economic Issues of Compulsory Health Insurance: Further Comment Get access D. Netzer D. Netzer Chicago, Illinois Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 66, Issue 4, November 1952, Pages 586–591, https://doi.org/10.2307/1882107 Published: 01 November 1952